Mentoring and the ministerial formation of seminary students - Chiroma, Nathan (Stellenbosch theological journal, 2017)
In this article I shall look at the role of mentoring and its relational nature in the ministerial formation of seminary students. Incorporating the relational nature of mentoring in ministerial formation it facilitates the integration of seminary students’ classroom experiences and their intellectual imaginations into practical ministerial skills in both the church and community. It is argued that embracing the relational nature of mentoring for ministerial formation in theological seminaries will help seminary students develop an awareness of the knowledge, skills and attitudes required for effective practical ministry. It will further help them develop an appreciation for their unique calling, gifting and skills. This article thus looks into how the relational nature of mentoring can foster the ministerial formation of seminary students.